2021
DOI: 10.1101/2021.03.12.435196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A natural mutator allele shapes mutation spectrum variation in mice

Abstract: Little is known about the impact of genetic variation on mutation rates within species. We conducted a QTL scan for alleles that influence germline mutagenesis using a panel of recombinant inbred mouse lines descended from the laboratory strains C57BL/6J (B6) and DBA/2J (D2). Mice inheriting D haplotypes at a locus on chromosome 4 accumulate C>A germline mutations at a 50% higher rate than those with B haplotypes. The QTL contains coding variation in Mutyh, a DNA repair gene that underlies C>A-dominated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…A recent study knocked out OGG1 in human cells and found that this elevated the rate of a C>A-dominated mutational signature known in the Cosmic catalog as SBS18 (Zou et al 2020). SBS18 was initially identified in tumors from individuals with pathogenic variation in Mutyh (Viel et al 2017), a direct interacting partner of OGG1 in the 8-oxoguanine repair pathway that has also been implicated in a C>A-dominated germline mutational signature in mice (Sasani et al 2021). Although our OGG1 plasmid assay provides compelling evidence that the 8-oxoguanine repair pathway plays a role in the AAR/AEQ mutator phenotype, we note that C>A mutations do not comprise all of the excess mutations measured in AEQ and AAR.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study knocked out OGG1 in human cells and found that this elevated the rate of a C>A-dominated mutational signature known in the Cosmic catalog as SBS18 (Zou et al 2020). SBS18 was initially identified in tumors from individuals with pathogenic variation in Mutyh (Viel et al 2017), a direct interacting partner of OGG1 in the 8-oxoguanine repair pathway that has also been implicated in a C>A-dominated germline mutational signature in mice (Sasani et al 2021). Although our OGG1 plasmid assay provides compelling evidence that the 8-oxoguanine repair pathway plays a role in the AAR/AEQ mutator phenotype, we note that C>A mutations do not comprise all of the excess mutations measured in AEQ and AAR.…”
Section: Discussionmentioning
confidence: 99%
“…The divergence of mutation spectra among human continental groups has been replicated in independently generated datasets ( 7 , 16 ), and similar patterns have been observed in other species, including great apes ( 17 ), mice ( 18 ), and yeast ( 19 ). Some of the mutation spectrum divergence between mice and yeast lineages has been mapped to mutator alleles ( 19 , 20 ).…”
mentioning
confidence: 99%
“…A recent study knocked out OGG1 in human cells and found that this elevated the rate of a C>A-dominated mutational signature known in the Cosmic catalog as SBS18 (Zou et al 2020). SBS18 was initially identified in tumors from individuals with pathogenic variation in Mutyh (Viel et al 2017), a direct interacting partner of OGG1 in the 8-oxoguanine repair pathway that has also been implicated in a C>A-dominated germline mutational signature in mice (Sasani et al 2021).…”
Section: Discussionmentioning
confidence: 99%